Creating political commitment for antimicrobial resistance in developing countries - Bhatia, Rajesh; Katoch, Vishwa; Inoue, Hajime (Indian journal of medical research (New Delhi, India : 1994), 2019)
[...]AMR has been a subject for discussion and swift action in the United Nations General Assembly [1] and several other economic and political fora. The economic impact of AMR is staggering. [...]2050, the cost of inaction to combat AMR shall approximate USD $100 trillion with a decline in global gross domestic product on 3.5 per cent; 28 million people are likely to be pushed into poverty due to AMR [7]. The comprehensive programme should include several actions directed towards improved healthcare infrastructure; ethical drug promotion; surveillance of AMR and antibiotic use in all sectors, prudent antibiotic use in humans and animals; effective infection prevention and control practices; antibiotic stewardship programmes in all healthcare facilities; and appropriate management of patients with resistant organisms through an efficient health system. Discovery, development and distribution of novel antimicrobials and associated business models face unique technical, financial, and ethical challenges. Because drug development is a resource-intensive process, the developed world must lead in this area.